Preparation and optical properties of samaria‐doped yttria‐stabilized zirconia single crystals. Issue 11 (29th May 2019) - Tan, Xiaojun; Xu, Shoulei; Wang, Xiangyu; Liu, Fenhong; Goodman, Bernard A.; Xiong, Dingkang; Deng, Wen
Abstract: Single crystals of yttria‐stabilized zirconia (YSZ) doped with various concentrations of Sm2 O3 were synthesized by the optical floating zone method, and their structure and spectroscopic properties characterized using powder X‐ray diffraction (XRD), optical absorption, and luminescence measurements. XRD showed that the cubic phase of ZrO2 was stabilized by addition of Y2 O3 and a series of absorption peaks characteristic of Sm 3+ was detected by UV‐visible absorption spectroscopy. Three phenomenological J‐O oscillator strength parameters Ωt ( t = 2, 4, 6) were calculated to evaluate the local structure and bonding in the vicinity of the Sm 3+ for the 0.75 mol% Sm2 O3 : YSZ sample. These were in order of Ω2 < Ω4 < Ω6 with values of Ω2 = 5.46 × 10 −20 cm 2, Ω4 = 10.70 × 10 −20 cm 2, and Ω6 = 12.67 × 10 −20 cm 2, and indicate a relatively high symmetry and low covalent character for the Sm‐O bond at the Sm 3+ sites in the YSZ matrix. Photoluminescence spectra recorded under an excitation of 404 nm showed four emission bands centered at 571 nm, 621 nm, 652 nm, and 716 nm corresponding to the transitions 4 G 5/2 → 6 Hj ( j = 5/2, 7/2, 9/2, 11/2). The transition probability, lifetime, and branching ratio obtained from the emission spectrum of the 0.75 mol% Sm2 O3 : YSZ crystal showed that YSZ is a potential host for Sm 3+ to achieve a reddish‐orange laser output, and the Sm 3+ ‐modified YSZ crystals have a possible use in reddish‐orange laser and lighting devices. Abstract : XRD showed that the cubic phase of ZrO2 was stabilized by addition of Y2O3. The room temperature photoluminescence excitation spectra of Sm2O3‐doped YSZ single crystals monitored with an emission wavelength of 606 nm contain several bands distributed around 302, 343, 361, 373, 404, 415, 435, 462, 478, 494, and 531 nm, and these are assigned to the Sm3+ ƒ→ƒ forbidden transitions from the 6H5/2 ground state to the 4P5/2, 4K15/2, 4D3/2, 4P7/2, 4F7/2, 6P5/2, 4G9/2, 4I13/2, 4I11/2, 4G7/2, and 4F3/2 excited states, respectively. Photoluminescence spectra recorded under an excitation of 404 nm showed four emission bands centered at 571 nm, 621 nm, 652 nm, and 716 nm corresponding to the transitions 4G5/2→6Hj (j = 5/2, 7/2, 9/2, 11/2).